(untitled) (Research, Society and Development, 2022)
Objective: it was detailed, through an integrative review, as the main assistance resources to Flosser in the removal of interdental biofilm in children, compared to conventional dental floss. Methodology: This study is an integrative review on the use of conventional flossing and flossing flosser for the removal of dental biofilm. For this, studies from electronic databases were consulted, from 2012 to 2022. Results: These patients elected to compose the tables, presented patients with pediatric studies, in which, diseases arising from plaque, with ages ranging from zero to 17 years. The detailing of these guidelines is defined as the main pathologies addressed, if the specific instructions in the studies are also not correct, in addition to guidelines in the school environment. In addition, a survey is made of which dental floss was mentioned in the studies, and the result of this use, or lack of it. Conclusion: It is a fact, as the most common diseases that can arise with insufficient management or the total absence of it, caries and periodontal disease, in children, this scenario is more worrying, as there is a dependence on parents/guardians to perform. But, this being reversed with health promotion practices, with the dentist promoting oral health in schools, hospitals and offices.